1998
DOI: 10.1021/jp981820p
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Temperature Dependence in Surface-Enhanced Raman Scattering of 1-Propanethiol Adsorbed on a Silver Island Film

Abstract: Intensity of the surface-enhanced Raman scattering (SERS) of 1-propanethiol adsorbed on a silver film prepared chemically has been measured over the 15-300 K surface temperature range. A reversible change in the SERS intensity with the temperature has been observed, with the intensity at 15 K being larger than that at 300 K by a factor of ∼3. Various factors that can affect the SERS intensity such as the laser-induced change in surface morphology, adsorption and desorption, and destruction of adatoms could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 45 publications
5
38
1
Order By: Relevance
“…[105][106][107] One method for reducing laser-induced molecular degradation is to lower the sample temperature. For example, by conducting SERS experiments at 40 K, Pang et al [108] have shown that the negative effects of laser exposure can be greatly reduced. In general, lowering the sample temperature has several desirable effects, such as: less sample degradation due to laser damage, better analyte adsorption, and a suppression of analyte diffusion, which, in the sm-SERS regime, results in fewer spectral fluctuations.…”
Section: à2mentioning
confidence: 99%
“…[105][106][107] One method for reducing laser-induced molecular degradation is to lower the sample temperature. For example, by conducting SERS experiments at 40 K, Pang et al [108] have shown that the negative effects of laser exposure can be greatly reduced. In general, lowering the sample temperature has several desirable effects, such as: less sample degradation due to laser damage, better analyte adsorption, and a suppression of analyte diffusion, which, in the sm-SERS regime, results in fewer spectral fluctuations.…”
Section: à2mentioning
confidence: 99%
“…As we know, SERS technologies are generally applied to two systems of adsorbates [9] and deposited species [10]. On the other hand, as shown in the literature, substrate-temperature dependences of SERS below and above room temperature were widely investigated through theoretical and experimental studies [11][12][13][14]. All of these studies indicate that the SERS enhancement in general decreases as substrate-temperature decreases.…”
Section: Introductionmentioning
confidence: 99%
“…In SERS studies, two different analysis systems of adsorbates [20] and deposited species [21] are generally employed. On the other hand, as shown in the literature, substrate-temperature dependences of SERS below and above room temperature were widely investigated through theoretical and experimental studies [22][23][24][25]. All of these studies indicate that the SERS enhancement in general decreases as substrate temperature decreases.…”
Section: Introductionmentioning
confidence: 99%